Trade in Developing East Asia: How It Has Changed and Why It Matters - Cristina Constantinescu; Aaditya Mattoo; Michele Ruta (East Asian Economic Review (EAER), 2018)
East Asia, for long the epitome of successful engagement in trade, faces serious challenges: technological change that may threaten the very model of labor intensive industrialization and a backlash against globalization that may reduce access to important markets. The analysis in this article suggests that how East Asia copes with these global challenges will depend on how it addresses three more proximate national and regional challenges. The first is the emergence of China as a global trade giant, which is fundamentally altering the trading patterns and opportunities of its neighbors. The second is the asymmetric implementation of national reform – in goods trade and investment versus services – which is affecting the evolution of comparative advantage and productivity in each country. The third is the divergence between the relatively shallow and fragmented agreements that regulate the region's trade and investment and the growing importance of regional and global value chains as crucial drivers of productivity growth.
Keywords: F13; F14; F15; F60; 330; Trade Policy; Goods Trade; Services Trade; China; Trade Agreements; Global Value Chains